2001
DOI: 10.1103/physrevlett.86.2227
|View full text |Cite
|
Sign up to set email alerts
|

Precise Measurement of the Positive Muon Anomalous Magnetic Moment

Abstract: A precise measurement of the anomalous g value, aµ = (g − 2)/2, for the positive muon has been made at the Brookhaven Alternating Gradient Synchrotron. The result a µ + = 11 659 202(14)(6) × 10 −10 (1.3 ppm) is in good agreement with previous measurements and has an error one third that of the combined previous data. The current theoretical value from the standard model is aµ(SM)= 11 659 159.6(6.7) × 10 −10 (0.57 ppm) and aµ(exp)−aµ(SM) = 43(16) × 10 −10 in which aµ(exp) is the world average experimental value… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
257
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(269 citation statements)
references
References 19 publications
10
257
1
1
Order By: Relevance
“…In this paper, we addressed the implications of this idea of "universal extra dimensions" for the muon anomalous magnetic moment. For one or two extra dimensions, we computed the one-loop contribution of the KK modes of the standard model fields and found that it is too small to be detected by the Muon (g − 2) experiment at BNL [6]. We then analyzed higher-dimension operators in the context of the 6-dimensional standard model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we addressed the implications of this idea of "universal extra dimensions" for the muon anomalous magnetic moment. For one or two extra dimensions, we computed the one-loop contribution of the KK modes of the standard model fields and found that it is too small to be detected by the Muon (g − 2) experiment at BNL [6]. We then analyzed higher-dimension operators in the context of the 6-dimensional standard model.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous section we showed that, with one or two universal extra dimensions, the value of g µ − 2 ≡ a µ induced by loops with standard model KK fields below the effective theory cutoff M s is smaller than the final expected 1σ sensitivity of the muon g − 2 experiment at BNL [6]. However, physics above M s also contributes to a µ , and these effects could be large given that the SU(3) C × SU (2) In six dimensions, the standard model is chiral as in four dimensions and is highly constrained by anomaly cancellation and Lorentz invariance.…”
Section: The 6-dimensional Standard Model and Short Distance Effects mentioning
confidence: 99%
“…For practically all the other (s)particles of the model one does now have some lower bounds on their masses from extensive phenomenological studies and searches both at colliders and in astroparticle experiments. One can for example mention the impact of both LEP and the Tevatron in constraining the model parameters through the direct searches, the importance of rare decays notably b → sγ or even low energy experiments like the recent measurement of the muon anomalous moment (g − 2) µ [4]. Cosmological considerations like the thermal relic density of the LSP also put some stringent bounds on the MSSM.…”
Section: Jhep03(2004)012mentioning
confidence: 99%
“…For the latter we include both the strong α s contribution as well as the Yukawa contribution for the SUSY Wilson coefficients as well as the charged Higgs and the Goldstone contribution. 4 Our standard model value (with scale parameters set at m b ), gives Br(b → sγ) = 3.72 × 10 −4 while the scale and other parameter uncertainty (α s , CKM matrix elements) are about 10%. To bound the SUSY contribution we take the world weighted average of the CLEO [65] BELLE [66] and ALEPH [67] measurements…”
Section: B → Sγmentioning
confidence: 99%
“…The muon g − 2 anomaly has been a long standing puzzle since the announcement by the E821 experiment in 2001 [1,2]. During the past 15 years, development in both experimental and theoretical sides has been made to reduce the uncertainties by a factor of two or so, and thus establish a consistent 3σ discrepancy.…”
Section: Introductionmentioning
confidence: 99%